The Effect of corrosion on the quality repair of the aluminum alloy A 5083 H11 by bonded composites (Fracture and Structural Integrity, 2020)
In this paper, the effect of corrosion on the performance of the bonded composite patch repair in aluminum alloy A5083 marine structure was investigated using three dimensional finite element methods. To this end, two patches made in carbon/epoxy and boron/epoxy, bonded on corroded plates with and without crack, were tested under different applied loads. The effect of both corrosion and cracked materials on the damage of the adhesive FM73, was also highlighted. The obtained results show that, the corrosion has a significant effect on the quality repair performance. Indeed, it is proved that, the rate of damage increases with the increase of the applied load, and is more significant in the case of plates cracked and repaired by carbon/epoxy patch. Hence, the best performances were obtained using boron/epoxy patches
Keywords: Corrosion; Damage zone; Composite patch; Aluminum alloy; Adhesive; Crack